2011
DOI: 10.1007/s10916-011-9798-7
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone App Use Among Medical Providers in ACGME Training Programs

Abstract: The past decade has witnessed the advent of the smartphone, a device armed with computing power, mobility and downloadable "apps," that has become commonplace within the medical field as both a personal and professional tool. The popularity of medically-related apps suggests that physicians use mobile technology to assist with clinical decision making, yet usage patterns have never been quantified. A digital survey examining smartphone and associated app usage was administered via email to all ACGME training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
370
3
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(398 citation statements)
references
References 5 publications
14
370
3
11
Order By: Relevance
“…These include portability, continuous internet connectivity, enough computing power to run complex applications and the simple fact that the majority of doctors have one in their pocket. 4 The capacity for clinical use of smartphone technology is being increasingly documented in the medical literature. The assessment of wounds by picture messaging has become ubiquitous amongst plastic surgeons, and studies have found promising results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include portability, continuous internet connectivity, enough computing power to run complex applications and the simple fact that the majority of doctors have one in their pocket. 4 The capacity for clinical use of smartphone technology is being increasingly documented in the medical literature. The assessment of wounds by picture messaging has become ubiquitous amongst plastic surgeons, and studies have found promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones have enabled volumes of medical literature and reference material to be accessible to students and clinicians in the palm of their hand. 4 A recent survey amongst medical trainees found that 485% of respondents use a smart phone, and of these, the most popular was the iPhone. 4 One of the reasons for the iPhone's popularity amongst medical professionals is the rapidly growing 'App Store', which has the largest collection of applications amongst any device, and currently boasts 4500 000 applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers are encouraged to read 'Electronic health records in ambulatory care' by DesRoches et al 13 , 'New horizons for health through mobile technologies' a World Health Organisation report 14 , and 'Smartphone App use among medical providers in ACGME training programs'. 15 Hopefully this will stimulate ideas and facilitate high-quality surveys related to mobile technologies in medical practice.…”
Section: Resultsmentioning
confidence: 99%
“…In cardiology, a number of applications have been developed to monitor clinically important parameters including heart rate variability and arrhythmias. 14 In neurosurgery, apps that enable clinicians to accurately position ventricular catheters from CT scans have been developed. 15 Despite the growing body of literature regarding mHealth, recent meta-analyses have shown that there are currently few studies based on high methodological quality.…”
Section: Current Evidencementioning
confidence: 99%